2020
DOI: 10.1177/1357633x19899237
|View full text |Cite
|
Sign up to set email alerts
|

Patient perception of physician empathy in stroke telemedicine

Abstract: Introduction We assessed patients’ perceptions of physician empathy during telemedicine consultations as compared to in-person consultations during clinical encounters for acute stroke. Methods This prospective cohort study was undertaken at a comprehensive stroke centre hub in collaboration with a distant community hospital spoke site. Eligible participants presented to hub or spoke emergency departments with suspected acute stroke within three hours of symptom onset. Participants were evaluated at the hub si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 31 publications
3
46
0
1
Order By: Relevance
“…Similarly, successful programs have been undertaken worldwide, such as telestroke programs in Hawaii and South California ( 28 ). There is also evidence to suggest that patients who receive acute stroke assessment through telemedicine do not perceive decreased physician empathy compared to those who receive physical consultation ( 29 ). This somewhat relieves concerns about impaired patient–physician connection through telemedicine.…”
Section: Telemedicine In Emergency Cases and Triagementioning
confidence: 99%
“…Similarly, successful programs have been undertaken worldwide, such as telestroke programs in Hawaii and South California ( 28 ). There is also evidence to suggest that patients who receive acute stroke assessment through telemedicine do not perceive decreased physician empathy compared to those who receive physical consultation ( 29 ). This somewhat relieves concerns about impaired patient–physician connection through telemedicine.…”
Section: Telemedicine In Emergency Cases and Triagementioning
confidence: 99%
“…The collaborative care model includes the provision of specialist psychiatric services from urban health centers by engaging primary care physicians in the evaluation and treatment of patients in the remote locale using a digital platform. Most studies 7 , 8 , 11 , 14 16 showed that this model is cost-effective. The conventional integrated care models have often suffered insufficient funding, lack of continued support from psychiatrists, limited coverage of mental disorders during the training, and monitoring.…”
Section: Dawn Of Telepsychiatrymentioning
confidence: 99%
“…For musculoskeletal assessments, clinicians cannot rely on passive physical testing; notably, however, this should not be the dominant source of clinical evidence during in-person practice either. 17 , 87 Gaining a thorough understanding of a patient's condition through robust questioning underpins good assessment and can be achieved remotely.…”
Section: Resultsmentioning
confidence: 99%